STUDI REVIEW KETATA NEGARAAN DALAM PENYELENGGARAAN PEMILIHAN UMUM - HIDE WULAKADA, IMAM AL GHOZALI (Dinamika Hukum, 2020)
This research is motivated by the state of democracy which has not been carried out properly. Then this research is intended to find out the philosophy of state administration, Pancasila constitution and its implementation in the General Election. Doctrinal research methods with a kind of explanatory approach, which places Pancasila and the 1945 Constitution as the main reference in studies and analysis. By reviewing a number of constitutional articles in the 1945 Constitution, this study and analysis resulted in three points, namely (1) Eliminating the position of Political Parties as participants in legislative elections, (2) Eliminating the position of political parties in the faction in the MPR, (3) Changing the Parliamentary system from bicameral to be unicameral. Keywords: Election of People's Representatives without Political Parties